2011
DOI: 10.1007/s10103-011-0895-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of narrowband ultraviolet B phototherapy on serum folic acid levels in patients with psoriasis

Abstract: Narrowband ultraviolet B phototherapy (NB-UVB) is a widely used modality in the treatment of psoriasis and is generally accepted as safe in pregnancy. Previous studies have described photodegradation of serum folate after exposure to UVA radiation but the effect of UVB is not known. We studied the effect of NB-UVB phototherapy on serum folic acid levels in patients with psoriasis and the relationship between changes in serum folate levels and the total cumulative dose of NB-UVB. Included in the study were 30 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 10 publications
1
39
2
5
Order By: Relevance
“…With a possible mean loss in folate levels of up to 27% while Patient 3 was on nb-UVB over 18 treatments [38], This patient's psoriasis flared on 1 mg daily folic acid but cleared slightly when given 4 mg a day.…”
Section: Commentmentioning
confidence: 94%
“…With a possible mean loss in folate levels of up to 27% while Patient 3 was on nb-UVB over 18 treatments [38], This patient's psoriasis flared on 1 mg daily folic acid but cleared slightly when given 4 mg a day.…”
Section: Commentmentioning
confidence: 94%
“…The data regarding the safety of NBUVB treatment in pregnant women comes from its use in pregnant psoriasis patients. But recently it has been shown that patients with high cumulative NBUVB doses have a decrease in serum folic acid levels [49]. This finding is especially important for the pregnant women as they usually need folic acid supplementation to prevent neural tube defects.…”
Section: Phototherapy and Lasersmentioning
confidence: 99%
“…71 Apesar disso, os níveis séricos maternos de ácido fólico podem sofrer redução com altas doses cumulativas de fototerapia UVB. [72][73][74] Por sua vez, a deficiência de ácido fólico no primeiro trimestre pode predispor ao desenvolvimento de defeitos do tubo neural. 72,74 Assim, as doentes grávidas que recebam tratamentos de fototerapia UVB devem ser submetidas ao doseamento regular dos níveis de ácido fólico, especialmente durante o primeiro trimestre da gravidez.…”
Section: Fototerapia Ultravioleta Bunclassified
“…[72][73][74] Por sua vez, a deficiência de ácido fólico no primeiro trimestre pode predispor ao desenvolvimento de defeitos do tubo neural. 72,74 Assim, as doentes grávidas que recebam tratamentos de fototerapia UVB devem ser submetidas ao doseamento regular dos níveis de ácido fólico, especialmente durante o primeiro trimestre da gravidez. 73 É importante saber que o aumento da temperatura corporal central da grávida durante o primeiro mês da gestação pode aumentar o risco de defeitos do tubo neural fetais.…”
Section: Fototerapia Ultravioleta Bunclassified